Investigating the Safety Culture and Costs Arising from Safety Non-Compliance on Building Sites - Hedayat, Amir Ahmad; Shahniani, Mesyam (Journal of History Culture and Art Research, 2017)
In addition to the positive effects of industrial development and technological progress, it also has adverse side effects such as increasing the quantity and quality of working and living environment pollution. Work-related accidents and occupational diseases are the consequences of the development of industry and technology and they increasingly threaten human life, especially the staff. Work-related Accidents are accidents that occur in the line of duty in the workplace and lead to fatal or non-fatal injuries. Although many activities have been done to reduce work-related, or in other words occupational accidents, the accident statistics is still high, in a way that The World Health Organization considered that as an epidemic in the area of public health, and considered that as a critical risk factor for health, economic and social issues. This paper deals with safety culture, costs arising from accidents and how to cope with the work-related accidents.